Investigation of Ultrafast Carrier Dynamics in InGaN/GaN‐Based Nanostructures Using Femtosecond Pump–Probe Absorption Spectroscopy. Issue 10 (29th July 2021) - Aggarwal, Tarni; Udai, Ankit; Banerjee, Debashree; Pendem, Vikas; Chouksey, Shonal; Saha, Pratim; Sankaranarayanan, Sandeep; Ganguly, Swaroop; Bhattacharya, Pallab; Saha, Dipankar
Abstract : GaN‐based optoelectronic devices including light‐emitting diodes and lasers realized with quantum‐confined nanostructures, revolutionized the solid‐state lighting. Excited‐state ultrafast nonlinear dynamics of these nanostructures are crucial in determining the device performance in terms of luminescence efficacy, emission spectra, wall‐plug efficiency, turn‐on delay, lasing threshold current, and modulation bandwidth. Therefore, understanding the carrier and photon dynamics of these nanostructures is of utmost importance. A comparative investigation of ultrafast nonlinear carrier‐photon dynamics of 2D, 1D, and 0D InGaN/GaN nanostructures is carried out. Femtosecond pump–probe absorption spectroscopy is used uniformly herein to obtain the wavelength‐dependent ultrafast kinetics of these nanostructures, with a temporal resolution of ≈50 fs. Carrier thermalization and relaxation processes of all the samples are studied both experimentally and theoretically. Distinguished phenomena, such as fast carrier trapping and subsequent detrapping of the carriers from sub‐bandgap defect states are observed. Real‐time monitoring of quantum confined Stark effect, enhanced radiative recombination, and diffusion‐limited carrier kinetics are manifested. Carrier capture and recombination time constants are calculated theoretically, considering quantum properties. Theoretical values are in good agreement with the experimental observations. In addition, transient absorption spectroscopy is used to investigate and decouple the surface and the bulk properties of GaN surfaces. Abstract : III‐nitride‐based nanostructures find huge applications in optoelectronics including solid‐state lighting, high‐speed communication, data interconnects, and many more. Nonlinear carrier and photon dynamics are crucial in optimizing the device performance. Herein, the ultrafast dynamics of InGaN/GaN nanostructures using femtosecond pump–probe absorption spectroscopy is explored. Extensive theoretical calculations of associated capture and recombination time constants are carried out.